2022
DOI: 10.3390/ijms232416002
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil in the Mediterranean Diet and Its Biochemical and Molecular Effects on Cardiovascular Health through an Analysis of Genetics and Epigenetics

Abstract: Human nutrition is a relatively new science based on biochemistry and the effects of food constituents. Ancient medicine considered many foods as remedies for physical performance or the treatment of diseases and, since ancient times, especially Greek, Asian and pre-Christian cultures similarly thought that they had beneficial effects on health, while others believed some foods were capable of causing illness. Hippocrates described the food as a form of medicine and stated that a balanced diet could help indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Within this context, individual fatty acids from vegetable oils, as well as oil-soluble bioactive compounds, may play a different role in human health, especially for the management of acute and chronic diseases, such as cardiovascular disease, breast cancer, and inflammation [ 68 , 69 , 70 , 71 ]. One of the most examined oils for its health properties is olive oil [ 18 , 68 , 69 , 71 , 72 ]. Olive oil is rich in monounsaturated oleic acid and phenolic compounds, as well as squalene [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this context, individual fatty acids from vegetable oils, as well as oil-soluble bioactive compounds, may play a different role in human health, especially for the management of acute and chronic diseases, such as cardiovascular disease, breast cancer, and inflammation [ 68 , 69 , 70 , 71 ]. One of the most examined oils for its health properties is olive oil [ 18 , 68 , 69 , 71 , 72 ]. Olive oil is rich in monounsaturated oleic acid and phenolic compounds, as well as squalene [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…From the early 1990s, well-structured clinical trials started to take place in hospitals to analyze the potential of omega-3 fatty acids against different pathologies. The effect of omega-3 fatty acids in patients undergoing coronary artery bypass graft Surgery [ 67 , 68 ], HIV-seropositive patients [ 69 , 70 , 71 ], patients with multiple sclerosis [ 72 , 73 ], children with attention deficit hyperactivity disorder [ 18 ], patients with Alzheimer’s disease [ 27 , 74 ], patients with prostate cancer [ 75 ], and patients on hemodialysis [ 76 , 77 ], was investigated. The administration of vitamins or n-3 (PUFAs) in patients undergoing coronary artery bypass graft (CABG) surgery attenuated post-operative oxidative stress during CABG surgery [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…This observation has been confirmed by several subsequent studies, which provide strong evidence for the benefits of MD on cardiovascular health, including the reduction in the incidence of cardiovascular outcomes and risk factors, including obesity, hypertension, metabolic syndrome, and dyslipidemia [ 2 , 3 , 4 , 5 ]. Not only evidence from long-term observational studies but also clinical and preclinical studies demonstrated that the MD, closely linked to traditional areas of olive cultivation in the Mediterranean region, has been associated with low rates of chronic diseases, reductions in the incidence of some cancers, and neurodegenerative diseases; consequently, MD provides high adult life expectancy [ 2 , 6 , 7 , 8 , 9 ]. The traditional MD is described as a diet heavy in vegetable oils and low in saturated fat; it is commonly characterized by a high intake of fresh or minimally refined foods, such as cereals, vegetables, fruits, nuts, legumes, fish, olive oil, and red wine in moderation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only evidence from long-term observational studies but also clinical and preclinical studies demonstrated that the MD, closely linked to traditional areas of olive cultivation in the Mediterranean region, has been associated with low rates of chronic diseases, reductions in the incidence of some cancers, and neurodegenerative diseases; consequently, MD provides high adult life expectancy [ 2 , 6 , 7 , 8 , 9 ]. The traditional MD is described as a diet heavy in vegetable oils and low in saturated fat; it is commonly characterized by a high intake of fresh or minimally refined foods, such as cereals, vegetables, fruits, nuts, legumes, fish, olive oil, and red wine in moderation [ 9 , 10 ]. Individual foods and components of MD (e.g., extra-virgin olive oil and nuts) have numerous health-promoting properties [ 11 , 12 , 13 , 14 , 15 , 16 ], as they are rich in polyphenols, flavonoids, phenolic acids, and other bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Extra virgin olive oil (EVOO) is the main source of fat in the Mediterranean diet (MD), the most studied dietary pattern globally. [1] Adherence to a MD and primary consumption of increase in plasma total cholesterol (TC) and LDL cholesterol (LDLc) levels in apolipoprotein (APO)E-deficient mice fed with an olive oil-supplemented diet. [11] Further, excessive olive oil use could alter lipid metabolism in humans.…”
Section: Introductionmentioning
confidence: 99%